Alteraciones Hepaticas en pacientes con infección por VIH en un centro de investigacion en Bogotá Colombia 2009 - 2019 - Santiago Sánchez-Pardo (Asociación Colombiana de Infectología, 2021)
Introduction: Alterations in liver biochemistry are frequent in patients with HIV infection, the etiology is varied and includes multiple causes, liver steatosis is one of the most frequent with an estimated prevalence of 60% after the appearance of antiretroviral treatment Objectives: To characterize liver disorders in a series of patients with HIV infection at a research center in Bogotá Colombia during the period 2009-2019. Materials and Methods: Descriptive, retrospective, observational study of patients with HIV infection who attended adisease research center during the years 2009-2019. Results: 67 clinical histories werereviewed, 94% were men and 6% women with an average age of 44 years, 92.5% of the patients had use of anti-retroviral therapy and the diagnosis of HIV was known 11.7 yearsago on average. The main liver diseases were HIV-Hepatitis C coinfection and fatty liver inequal percentages, 31.3%. The average HOMA index was 2.58. Discussion: Liver diseases are an important cause of morbidity and mortality in patients with HIV infection. Viralcoinfections and fatty liver can be very frequent in our setting, unlike other studies. Conclusions:This is the first study locally to describe the liver disorders in patients withHIV, non-AIDS comorbidities, including fatty liver, play an important role in the disease and could behave like the general population. Hepatitis C continues to be a frequent coinfectionin the HIV population.